Compromised Sexual Health Among Male Patients With Implantable Cardioverter Defibrillator: A Cross-Sectional Questionnaire Study - Palm, Pernille; Zwisler, Ann-Dorthe; Svendsen, Jesper Hastrup; Giraldi, Annamaria; Rasmussen, Marianne Linnet; Berg, Selina Kikkenborg (Sexual Medicine, 2019)
Abstract Introduction In cardiac patients with implantable cardioverter defibrillator (ICD), sexual function is sparsely described. Aim To determine the prevalence and distribution of sexual dysfunction, and to describe whether primary or secondary prophylactic ICD indication and antitachycardia pacing (ATP) or shock is associated with sexual function. Methods A cross-sectional survey of men with an implanted ICD was conducted at 2 university hospitals in Denmark. Inclusion criteria were men over the age of 18 with an ICD. Exclusion criterion was no partner. Main Outcome Measure Sexual function was assessed by the International Index of Erectile Function questionnaire and data on implantation indication (primary/secondary prevention) and therapy such as ATP and shock (both appropriate and inappropriate) was obtained from the Danish ICD Register. Results Data from 415 questionnaires were analyzed (response rate 50.2%). Patients had a mean age of 63.9±12.1 years. Erectile dysfunction (ED) was present in 70% of patients, orgasmic dysfunction was present in 57.9% of patients, 82.8% had reduced sexual desire, 85.8% had intercourse satisfaction problems, and 76.9% experienced overall satisfaction problems (non-validated metric except for ED). Patients with an ICD on primary prophylactic indication had more sexual dysfunction and ED compared with patients with an ICD on secondary prophylactic indication. ATP therapy, but not shock, was associated with more ED. Conclusion Sexual dysfunction is common in patients with ICD and is not limited to ED, but also orgasmic function, desire, intercourse, and overall satisfaction are affected. Primary prophylactic ICD indication and ATP, but not shock therapy, is associated with compromised sexual function.